Translating meaning as cognitive socio-cultural systems.A conceptual approach to the translation of plurilingualism in postcolonial literary discourse in Portuguese - Hernández, Rebeca (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Recent approaches to language, meaning and cognition contend that par-ticipants in linguistic interaction construct a mental representation of their understanding of discourse on the basis of linguistic expressions, world or experiential knowledge, socially-shared beliefs, and the imagination. Fo-cusing on the implications the coexistence of different languages has for the construction of a cognitive culture system, this paper argues that choosing monolingualism for the translation of postcolonial plurilingual texts impos-es semantic limitations, which may result in a dissimilar, domesticated, representation of the recreated reality. Besides taking an ethical stand, this paper also claims that preserving the plurilingualism of these texts responds to the wish to invite readers to open new mental spaces, where the cognitive system of the translated culture can be located. The analysis of examples from the translation into English of postcolonial texts in Portuguese will show strategies to achieve this aim.